Mutations in the Dimer Interface of Dihydrolipoamide Dehydrogenase Promote Site-specific Oxidative Damages in Yeast and Human Cells - Vaubel, Rachael A. (American Society for Biochemistry and Molecular Biology, 2011)
Dihydrolipoamide dehydrogenase (DLD) is a multifunctional protein well characterized as the E3 component of the pyruvate dehydrogenase and α-ketoglutarate dehydrogenase complexes. Previously, conditions predicted to destabilize the DLD dimer revealed that DLD could also function as a diaphorase and serine protease. However, the relevance of these cryptic activities remained undefined. We analyzed human DLD mutations linked to strikingly different clinical phenotypes, including E340K, D444V, R447G, and R460G in the dimer interface domain that are responsible for severe multisystem disorders of infancy and G194C in the NAD(+)-binding domain that is typically associated with milder presentations. In vitro, all of these mutations decreased to various degrees dihydrolipoamide dehydrogenase activity, whereas dimer interface mutations also enhanced proteolytic and/or diaphorase activity. Human DLD proteins carrying each individual mutation complemented fully the respiratory-deficient phenotype of yeast cells lacking endogenous DLD even when residual dihydrolipoamide dehydrogenase activity was as low as 21% of controls. However, under elevated oxidative stress, expression of DLD proteins with dimer interface mutations greatly accelerated the loss of respiratory function, resulting from enhanced oxidative damage to the lipoic acid cofactor of pyruvate dehydrogenase and α-ketoglutarate dehydrogenase and other mitochondrial targets. This effect was not observed with the G194C mutation or a mutation that disrupts the proteolytic active site of DLD. As in yeast, lipoic acid cofactor was damaged in human D444V-homozygous fibroblasts after exposure to oxidative stress. We conclude that the cryptic activities of DLD promote oxidative damage to neighboring molecules and thus contribute to the clinical severity of DLD mutations.